REGULATORY MECHANISMS OF PROLACTIN BIOLOGICAL EFFECTS REALIZATION (review) - Stupak, I.I.; Lakhno, I.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The main processes of synthesis and secretion of prolactin as a basic lactation hormone are considered. The assumption about perspectives of bioelement exchange investigation for the optimization of preventive maintenance methods and treatment of hypohalactia is performed.